Small-Sided Games as a Methodological Resource for Team Sports Teaching: A Systematic Review - Fernández-Espínola, Carlos (Int J Environ Res Public Health, 2020)
New models for teaching sports have arisen in the last years, characterised by the use of more contextualised situations, modified games, tactical awareness, transference of technical–tactical learning and different teaching progression, among other aspects. In this regard, small-sided games must be highlighted, due to their ability to integrate physical fitness, technique and tactical behaviour stimuli in similar conditions to the real game. Therefore, the aim of this systematic review was to analyse and describe the methodological possibilities that SSGs can provide regarding the teaching of technical–tactical aspects in team sports at young ages. The guidelines of the PRISMA declaration were followed with the purpose of conducting a systematic search. The search was performed in the databases Pubmed, Web of Science, Scopus and SportDiscus. From the 451 identified in an early phase, plus the 20 found in the references of other studies, only 47 met the inclusion criteria and were selected. The results yielded scientific evidence that justifies the use of small-sided games as a methodological resource for sports teaching at young ages. Among the main reasons, it can be highlighted that a reduction in the number of players and in the size of the pitch area increases the total ball contact per player and, therefore, the number of technical actions. Moreover, the intentional modification of certain rules helps to develop some sport training fundamentals.